Proposta de coleta seletiva da fração orgânica dos resíduos sólidos domiciliares visando sua utilização para a geração de biogás a partir da biodigestão anaeróbia - Oliveira, Francisco Diego Araújo (2015)
The National Solid Waste Policy recommends that, in adequate final disposal, only unserviceable waste should be released, which it is not the case of organic waste that accounts more than half of the municipal solid waste generation in the country. In this context, this research aimed to develop a proposal for a selective collection of the organic fraction of household solid waste (OFHSW) in Pici neighborhood, Fortaleza-CE, aiming its use for the generation of biogas from the anaerobic digestion. This research occurred in 05 (five) steps, namely: the development of the environmental education (EE) program; physical characterization of household solid waste (HSW); the implementation of a selective collection program of OFHSW; the physical and chemical characterization of OFHSW; and the anaerobic biodegradability tests. Initially, a socio-environmental questionnaire was applied to a total of 175 residences, in which most of its residents presented favorable socioeconomic characteristics for the development of this project. The HSW sampled showed a high average of per capita generation (0.93 Kg/hab.dia), low apparent specific weight (average of 156 Kg/m³) and high percentage of organic matter (average of 55.9%). In regard to the participation in the selective collection program, there was a potential participation of 61% of the residences, from which 33% effectively donated a clean OFHSW. The OFHSW showed slightly acidic characteristics, consisting of 74% moisture and 26% of TS, being basically composed of putrescible organic matter (VS = 92.15% TS on average) and rich in nutrients (average of TP= 0.68% and TKN = 1.43%). In biodegradability tests to analyze the effect of operating conditions, better results were found of SMA, biogas production and composition and COD removal in the flasks incubated at a speed of 150 rpm and with addition of 1 g/L of alkalizing. The pretreatment type that provided a higher biodegradability of OFHSW was the thermal one, in which the matter was exposed to a 30 minutes process of autoclaving, where were identified the largest removals of VS (41% removed), COD (56% removed) and value of SMA (1.0777 gCOD-CH4/gVS.d). It is also emphasized that in all the biodegradability tests, about 60% or more of the biogas composition was methane. It was observed that EE actions were able to provide a representative participation of the population in the OFHSW segregation